The Mediating Role of Customer Satisfaction in the Relationship between Experiential Marketing and Revisit Intention among Visitors of Bobocabin Kintamani - Putu Ika Putri Ardiani; Tjokorda Gede Raka Sukawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Camping has become a part of the lifestyle of modern tourists. From camping, a new lodging innovation emerged that combines hotel accommodation facilities and camping, namely glamping. One of the modern glamping in Bali is Bobocabin Kintamani. The purpose of this study was to analyze the effect of experiential marketing on revisit intention mediated by customer satisfaction. The sample of this study was 120 respondents of Bobocabin Kintamani visitors. The sampling technique that will be used in this study is purposive sampling. This research technique uses path analysis, Sobel test and VAF test. The results of this study indicate that experiential marketing has a positive and significant effect on revisit intention, experiential marketing has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on revisit intention, and customer satisfaction mediates experiential marketing on revisit intention. The implications of this study provide implications that can be used by Bobocabin Kintamani in developing appropriate strategies. Experiential marketing implemented by Bobocabin Kintamani plays an important role in increasing customer satisfaction, which ultimately has a positive impact on the intention to revisit. The unique experiences offered, such as the smart cabin concept with soothing natural views, increase customer satisfaction and form a lasting impression that encourages them to return.